Segregation and Life Satisfaction - Montero, Rodrigo; Vargas, Miguel; Vásquez, Diego (Frontiers in Psychology, 2021)
Our aim is to cast light on socioeconomic segregation effects on subjective wellbeing. In order to test our hypothesis, we use survey data from Chile (CASEN) for the years 2011 and 2013. We use the Duncan index to measure segregation based on income at the municipality level for 324 municipalities. The subjective wellbeing is obtained from the CASEN survey which considers a question about self-reported wellbeing. Segregation’s impact upon subjective wellbeing is not clear at first glance. On one hand, there is the evidence telling that segregation’s consequences are negative due to the spatial concentration of poverty and all the woes related to it. On the other hand, segregation would have positive effects because people may feel stress, unhappiness, and alienation when compare themselves to better-off households, additionally, there is previous evidence regarding the fact that people prefer neighboring people of a similar socioeconomic background. Hence an empirical test is needed. In order to implement it, we should deal with two problems, first, the survey limited statistical significance at the municipal level, hence we use the small areas estimation methodology to improve estimations’ statistic properties, and second, the double causality between segregation and subjective wellbeing, to deal with the latter we include lagged subjective wellbeing as a regressor. Our findings indicate that socioeconomic segregation has a positive effect on subjective wellbeing. This result is robust to different econometric specifications.